Relationship between Family History of Diabetes Mellitus and Gestational Diabetes Mellitus: A Meta-Analysis - Ammutammima, Ummu Fatihah; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Gestational Diabetes Mellitus (GDM) is the most common metabolic disorder first diagnosed during pregnancy. According to the American Diabetes Association (ADA) in 2006, GDM occurred in 7% of pregnancies each year. Family history of diabetes is an important risk factor for GDM. The relationshipbetween family history of DM and GDM has been investigated in several primary studies with several contradictions in the outcome. Therefore, this study aimed to determine the relationship between family history of diabetes and GDM using a meta-analysis method.Subjects and Method: The meta-analysis was conducted by systematically reviewing articles published from 2007 to 2020 from the Pubmed, Google Scholar, Science Direct, and ResearchGate databases. The keywords were